2007
DOI: 10.1186/1476-4598-6-62
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear localization of beta-catenin involved in precancerous change in oral leukoplakia

Abstract: Background: Oral leukoplakia is a precancerous change developed in the oral mucosa, and the mechanism that oral leukoplakia becomes malignant through atypical epithelium is not known. Here we compared the β-catenin expression detected by immunohistochemical staining in the normal oral epithelium and in the oral leukoplakia with or without dysplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
60
0
11

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 24 publications
8
60
0
11
Order By: Relevance
“…The absence of membranous and subsequent intracellular expression of β-catenin was 16 found to be a key event in oral cancer [9]. In the present study, absence of membranous and intense intracellular expression of β-catenin was mainly observed in oral carcinoma and CAL27 cells which were concurrent with earlier reports by Ishida et al [9] and Kobayashi et al [33].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The absence of membranous and subsequent intracellular expression of β-catenin was 16 found to be a key event in oral cancer [9]. In the present study, absence of membranous and intense intracellular expression of β-catenin was mainly observed in oral carcinoma and CAL27 cells which were concurrent with earlier reports by Ishida et al [9] and Kobayashi et al [33].…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, absence of membranous and intense intracellular expression of β-catenin was mainly observed in oral carcinoma and CAL27 cells which were concurrent with earlier reports by Ishida et al [9] and Kobayashi et al [33]. This suggests that the β-catenin pathway might be re-activated and involved in oral carcinogenesis.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Loss of membranous ß-catenin and E-cadherin associated with EMT have been shown to correlate with metastatic formation and poor prognosis in multiple solid tumors and is a common feature of OSCC (Kudo et al, 2004;Odajima et al, 2005;Tanaka et al, 2003;Wang and Ma, 2007;Williams et al, 1998). Several studies have demonstrated that cytoplasmic and nuclear localization of -catenin is correlated with tumor progression, invasion and metastatic potential of OSCC (Ishida et al, 2007;Lo Muzio et al, 1999;Odajima et al, 2005;Yu et al, 2005). Cytoplasmic/nuclear -catenin expression has also been found to significantly correlate with EGFR expression in OSCC (Odajima et al, 2005).…”
Section: Introductionmentioning
confidence: 96%
“…Quando presente no citoplasma, na ausência da ativação da via de sinalização de Wnt, a β-catenina é degradada por um complexo multiprotéico formado por APC, Axin e GSK3β. Porém, quando ocorre alguma mutação genética que ativa a via de sinalização de Wnt, a β-catenina deixa de ser degradada e acumula-se no citoplasma (MACDONALD; TAMAI; HE, 2009; SCHUSSEL; PINTO JÚNIOR; MARTINS, 2011;TIAN et al, 2011).Dessa forma a β-catenina pode translocar-se ao núcleo e atuar na transcrição de oncogenes envolvidos no aumento da proliferação celular, como a ciclina D1 (IWAI et al, 2005;ODAJIMA et al, 2005;ISHIDA et al, 2007;GONZALEZ-MOLES et al, 2014b).…”
Section: Figura 7 -unclassified